Electroless Ni-P deposition on WC powders through direct PdCl2 activation and study on the underlying mechanisms - Tang, Peng; Jiang, Shuwen; Yan, Jiawei; Li, Xianquan (Next materials, 2025)
The deposition of Ni-P on the surface of ceramic powders by the electroless method holds significant potential for enhancing the mechanical properties of the coating. In the conventional two-step electroless process, the utilization of tin chloride sensitization prior to palladium chloride activation for Ni-P deposition on ceramic particles in weak reducing systems is practically indispensable, as it enhances the secondary recovery of the plating solution by augmenting tin residues both on the powder surface and within the solution. Herein, we present a one-step direct activation of PdCl2 as an effective method for reducing Ni-P deposition on WC particles by facilitating adsorption on the low isoelectric point (I.E.P.) surface of WC particles. The strong negative surface charge facilitates the adsorption of palladium ions in the plating solution and thereby affording a lower elcetronic density, which facilating the Pd2 + reduced to form Pd0 species through the reduction of H2PO2- under a weak reducing system in chemical plating. The electroless plating for the deposition of nickel coatings on WC powders was realized through direct activation with PdCl2, thereby eliminating the conventional two-step SnCl2-PdCl2 pretreatment that requires pre-adsorption of Sn2+ from SnCl2 sensitization for activation.